Preliminary results of phase I trial of oral uracil/tegafur (UFT), leucovorin plus irinotecan and radiation therapy for patients with locally recurrent rectal cancer - Yasui, Masayoshi (BioMed Central, 2006)
BACKGROUND: Surgical attempts for locally recurrent rectal cancer often fail due to local re-recurrence and distant metastasis. Preoperative chemoradiation may enhance better local control and survival. The aim of this study was to assess the safety of oral uracil and tegafur (UFT) plus leucovorin (LV), and irinotecan combined with radiation and determine the maximum-tolerated dose (MTD) and dose limiting toxicity (DLT) of the triple drug regimen. PATIENTS AND METHODS: Patients with locally recurrent rectal cancer received escalating doses of irinotecan on days 1, 8, 15, and 22 (starting at 30 mg/m(2), with 10 mg increments between consecutive cohorts) and fixed doses of UFT (300 mg/m(2)) plus LV (75 mg/day) on days 3 to 7, 10 to 14, 17 to 21, and 24 to 28. Radiation was given 5 days per week totaling 40 to 50 Gy (2Gy/day). RESULTS: Six patients were treated at the starting dose, and 2 received the full scheduled chemoradiotherapy. The other 4 patients had grade 3 diarrhea and diarrhea was the DLT. One patient had partial response and he had subsequently radical surgical resection. Median progression free survival for local recurrence was 320 days. CONCLUSION: Irinotecan plus UFT/LV with concomitant radiotherapy in patients with locally recurrent rectal cancer was not feasible due to diarrhea in this setting. Modification of the treatment is needed.